2007
DOI: 10.1007/s10661-006-9264-z
|View full text |Cite
|
Sign up to set email alerts
|

Metals and radionuclides in birds and eggs from Amchitka and Kiska Islands in the Bering Sea/Pacific Ocean ecosystem

Abstract: Metals and radionuclide levels in marine birds of the Aleutians are of interest because they are part of subsistence diets of the Aleut people, and can also serve as indicators of marine pollution. We examined geographic and species-specific variations in concentrations of radionuclides in birds and their eggs from Amchitka, the site of underground nuclear tests from 1965 to 1971, and Kiska Islands (a reference site) in the Aleutians, and the levels of lead, mercury and cadmium in eggs. In 2004 we collected co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 43 publications
(37 reference statements)
1
7
0
Order By: Relevance
“…In a related study examining radionuclides and mercury in gulls ( Larus glaucescens ) and eiders ( Somateria mollissima ) from these same islands, we found that gull feather ( L. glaucescens ) levels were significantly higher for lead and manganese on Kiska than on Amchitka (Burger and Gochfeld 2007; Burger et al 2008). Thus, the finding of higher levels of lead on Kiska than on Amchitka was consistent for feathers of eiders, gulls, and puffins, birds of different trophic levels.…”
Section: Discussionmentioning
confidence: 78%
“…In a related study examining radionuclides and mercury in gulls ( Larus glaucescens ) and eiders ( Somateria mollissima ) from these same islands, we found that gull feather ( L. glaucescens ) levels were significantly higher for lead and manganese on Kiska than on Amchitka (Burger and Gochfeld 2007; Burger et al 2008). Thus, the finding of higher levels of lead on Kiska than on Amchitka was consistent for feathers of eiders, gulls, and puffins, birds of different trophic levels.…”
Section: Discussionmentioning
confidence: 78%
“…However, in a related study examining radionuclides and mercury in gull and eider ( Somateria mollissima ) eggs from these same islands, we found that gulls had significantly higher levels of mercury on Kiska than on Amchitka (Burger and Gochfeld 2007), but we did not analyze eggs from Adak (the island inhabited by Aleuts), nor did we analyze arsenic, chromium, manganese or selenium. Braune et al (2002) examined mercury levels in eggs of glaucous-winged gulls from the High Arctic, and showed that mercury levels increased with latitude; mercury levels ranged from 600 ppm to 4,900 ppm.…”
Section: Discussionmentioning
confidence: 83%
“…In tissues of seabirds from the Persian Gulf, concentrations of mercury in tissues of migratory birds were considerably higher than in resident birds (ZamaniAhmadmahmoodi et al 2009). Gulls had significantly higher levels of mercury than the eiders in the Bering Sea, and interspecific differences were detected due to differences in diet (Burger and Gochfeld 2007). Siberian gulls had greater metal concentrations in kidney, liver, pectoral muscle, and feather than Western reef heron from southern Iran (Mansouri et al 2012a, b).…”
Section: Introductionmentioning
confidence: 94%